COMMON SENSE ABOUT TOXOPLASMOSIS IN BRAZIL AND THE INVOLVEMENT OF THE CAT IN THE DISEASE CYCLE - Da Silva Firmo, Isabela; Paula Oliveira, Ana; Kallyla Costa Miranda, Kallyane; Gimenez Simão, Karoline; Satie Yamashiro Kanashiro, Leticia; Stancov, Priscilla (Journal of Interdisciplinary Debates, 2021)
The toxoplasmosis is a zoonosis caused by protozoan Toxoplasma Gondii and although cats play a main roll on the disease life cycle developing the protozoan by sexual reproduction, the contact with cats represents a low number of cases on transmission of the zoonosis, the main transmission is caused by the intake of infected food, like fruits, vegetables, raw or poorly cooked meat that may contain cysts. The study was developed aiming to evaluate the knowledge and preventive behavior regarding toxoplasmosis and link it with cats on the cycle of the zoonosis. A form was created with eight questions about it, 793 people participated, all located in national territory. Therefore, based on this information, we can confirm that, although most of the people that already have a college degree or is still finishing it, does not have knowledge about toxoplasmosis, whereas the majority still think that contact with cats is the biggest way to become infected.